Making the Health System Work for Nutrition (P10-139-19). (13th June 2019) - King, Shannon; Roberton, Timothy
Abstract: Objectives: The many factors underlying malnutrition highlight the need for nutrition strategies that are comprehensive and multi-sectoral. Within a multi-sectoral approach, the health system is uniquely placed to deliver ten nutrition-specific interventions, which, if scaled up, could substantially reduce under-5 deaths in high-burden countries (Bhutta et al, 2013). This study aims to clarify the role of key health system components, illuminating opportunities for increased uptake of nutrition-specific interventions and potential bottlenecks and challenges for programs and policies. Methods: We reviewed existing nutrition frameworks to develop a comprehensive logic model illustrating the causal pathways by which health system components influence household-level determinants of nutrition and individual-level health outcomes. Concurrently, we reviewed literature on health and nutrition interventions that have a proven, quantifiable impact on morbidity and mortality in low- and middle-income countries. We mapped data from the gathered literature onto the logic model, allowing us to identify key causal pathways for the delivery of nutrition-specific interventions, and highlighting areas where evidence is lacking. Results: There exists a large gap in the literature about how health system components influence the ability to delivery appropriate and high-quality nutrition care. Based on the nature of the intervention (i.e., supplement delivery, counselling, SAM/MAM management) several unique delivery pathways were identified and three common themes cut across all interventions: namely, the importance of a motivated and trained health workforce; reliable and efficient supply chains; and generating demand and increased care-seeking for nutrition interventions. Evidence from the broader health systems literature supports the importance of these three themes; however, this remains a research gap in the nutrition literature. Conclusions: Three core health system components - a health workforce, supply chain and demand generation - play a pivotal role in the delivery of nutrition interventions. A better understanding of these components in relation to nutrition, based on evidence, will help to improve the design and implementation of future nutrition programs. Funding Sources: Global Affairs Canada, under the project "Real Accountability: Data Analysis for Results".